Therapeutic and economic effects of multimodal back exercise: a controlled multicentre study - Müller, Gerhard; Bombana, Manuela (Journal of rehabilitation medicine, 2019)
To compare the cost-effectiveness of a multimodal back exercise programme for non-specific back pai...